Oat bran fiber protects against radiation-induced disruption of gut barrier dynamics and mucosal damage - Patel, Piyush; Jin, Chunsheng; Nookaew, Intawat; Robeson, Michael; Malipatlolla, Dilip K.; Devarakonda, Sravani; Rascón, Ana; Nyman, Margareta; Karlsson, Niclas G.; Wold, Agnes E.; Sjöberg, Fei; Bull, Cecilia (npj Biofilms and Microbiomes, 2025)
Dietary fibers are recognized for their health benefits, yet cancer patients undergoing pelvic radiotherapy are often advised to reduce fiber intake. This may negatively impact their bowel health. To evaluate the effects of dietary fibers on bowel health post-irradiation, male C57BL/6 mice were fed diets containing either 0 or 15% fiber with varying proportions of readily fermentable bioprocessed oat bran fiber and/or poorly fermentable microcrystalline cellulose, and either irradiated or sham-irradiated. Irradiation triggered mucus degradation and depletion of short-chain fatty acids, and a fiber-free diet exacerbated radiation-induced mucosal damage. In contrast, mice fed oat bran fiber exhibited less mucosal damage, fewer dysbiotic and mucus-degrading bacteria, higher production of short-chain fatty acids, and improved bactericidal activity. These benefits were dose-dependent, with 15% oat bran fiber providing greater protection. Our findings suggest that fiber deprivation exacerbates radiation-induced intestinal damage, while supplementation with 15% highly fermentable oat bran fiber supports mucosal integrity and protects against radiation-induced injury. (Figure presented.)